Bismarck in the bedroom? Pension reform and fertility: Evidence 1870-2010 - Philipp Jäger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Rising public pension generosity has frequently been cited as one reason for the (persistently) declining fertility rates in many advanced economies. Despite the theoretical appeal, empirical evidence on the pension-fertility nexus is limited. To fill this gap, I study country-level fertility trends before and after 23 pension reforms using a long-run panel dataset starting in 1870. In addition to the raw fertility rate (birth per women aged 15-49), I examine the residuals of a fertility regression, which capture variations in the fertility rate that cannot be explained by alternative theories of the historical fertility decline. Contrasting pre- and post-reform trends of the raw fertility rate as well as the fertility regression residual across countries, I do not find robust evidence that pension reforms, on average, affect fertility in the way most theoretical models predict. On the individual country level, however, some reforms are indeed associated with a significant structural break in fertility trends that is in line with the old-age security hypothesis. Varying social ties might provide an explanation for the different country-specific fertility reactions to pension reforms. – – Großzügige öffentliche Rentenversicherungssysteme werden häufig für rückläufige Fertilitätsraten verantwortlich gemacht, da sie möglicherweise Kinder als eine Form der Altersabsicherung verdrängen. Trotz der Plausibilität und der Relevanz dieses Arguments, existiert kaum empirische Forschung zum Thema. Um diese Lücke zu füllen, untersuche ich wie sich die Fertilitätsrate vor- und nach einer Reihe von Rentenreformen, angefangen bei der Einführung der öffentlichen Rentenversicherung im 19. Jahrhundert, entwickelt hat. Im Durchschnitt über alle Länder hinweg finde ich keine Evidenz dafür, dass die Einführung oder Erweiterung der öffentlichen Rentenversicherungssysteme die Fertilitätsrate nachhaltig reduziert hat. Die länderspezifischen Ergebnisse sind allerdings sehr heterogen. In einigen Ländern scheint die Einführung der Rentenversicherung sogar mit einer Steigerung der Fertilität einhergegangen zu sein (z.B. in Italien), während in anderen Ländern das Gegenteil zu beobachten ist (z.B. in Frankreich). Kulturelle Unterschiede in Bezug auf die Eltern-Kind-Bindung bilden einen möglichen Erklärungsansatz für die Heterogenität der Ergebnisse.
Keywords: H55; J13; 330; Old-age security; fertility; pension reform